Early language learning : a model for success - Saunders Semonsky, Carol M.; Spielberger, Marcia A. (Emerald Publishing Limited : Information Age Publishing, 2004)
The aim of this volume is to provide a detailed description of the process of initiating, maintaining and assessing a top quality elementary school foreign language program and to assist planners by providing them with a workable model. The book describes the successes and challenges of the Georgia Elementary School Foreign Languages Model Program. It includes a detailed description of the curriculum and of the research data showing positive effects of early language learning on elementary school students in Georgia. The primary audience for this book is policy makers, state and district level educators, including supervisors who have responsibility for foreign languages, principals, teachers and foreign language educators who are interested in components of best practices in early language learning education or who wish to begin a high quality elementary school foreign language program at the state or district level.
Keywords: Language and languages -- Study and teaching (Elementary) -- Georgia.; Education -- Teaching -- Subjects -- General.; Teaching of a specific subject.; elektronické knihy; electronic books